2004
DOI: 10.1002/jcb.10751
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive regulation and function of PI 3K/Akt and MAPKs in doxorubicin‐induced apoptosis of human lung adenocarcinoma cells

Abstract: Regulation and function of PI 3K/Akt and mitogen-activated protein kinases (MAPKs) in doxorubicin-induced cell death were investigated in human lung adenocarcinoma cells. Doxorubicin induced dose-dependent apoptosis of human lung adenocarcinoma NCI-H522 cells. Prior to cell death, both Akt and the MAPK family members (MAPKs: ERK1/2, JNK, and p38) were activated in response to the drug treatment. The kinetics of the inductions for Akt and MAPKs are, however, distinct. The activation of Akt was rapid and transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
2
29
1
Order By: Relevance
“…This is in agreement with the study by Zhao et al (2004) showing that the MAPK pathway is not involved in doxorubicininduced apoptosis of lung adenocarcinoma cells (Zhao et al, 2004). The effects of various cytotoxic agents may vary considerably depending on the cell type and the signalling pathway activity (Wang et al, 2000;Guise et al, 2001;Liu et al, 2001).…”
Section: Sensitization Of Mrp1-mediated Multidrug Resistance R Abdul-supporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the study by Zhao et al (2004) showing that the MAPK pathway is not involved in doxorubicininduced apoptosis of lung adenocarcinoma cells (Zhao et al, 2004). The effects of various cytotoxic agents may vary considerably depending on the cell type and the signalling pathway activity (Wang et al, 2000;Guise et al, 2001;Liu et al, 2001).…”
Section: Sensitization Of Mrp1-mediated Multidrug Resistance R Abdul-supporting
confidence: 92%
“…Activation of Ras signalling pathways is associated with the upregulation of target genes involved in drug transport (Chin et al, 1992;Zuber et al, 2000). Drug treatment may downregulate or activate signalling kinases, respectively (Nakashio et al, 2002;Zhao et al, 2004). Most importantly for the issue of therapy, enhanced sensitivity to drug treatment was observed in the presence of signalling inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…These findings agree well with recent studies showing that p38 MAPK is activated by doxorubicin and is required for doxorubicin-induced apoptosis in fibroblasts and cardiomyocytes [45][46][47], although possible involvement of Bcl-2 proteins was not considered in those investigations. Nevertheless, other researchers [48] found no change in p38 MAPK activity in breast cancer cells treated with doxorubicin, and it has been suggested that p38 MAPK protects lung cancer cells from apoptosis caused by doxorubicin [49]. Our data show that p38 MAPK mediates doxorubicin-induced endothelial apoptosis by inhibiting phosphorylation of Bad in a PI3-K/Akt-dependent manner and by downregulating Bcl-xL.…”
Section: Doxorubicin-induced P38 Mapk Activation Negatively Regulatescontrasting
confidence: 47%
“…We find that AF induces Akt phosphorylation at serine 473 (Figure 4a), which is required for Akt activity (Shieh et al, 2000;Sordet et al, 2003;Sarbassov et al, 2005). Akt has been shown to be activated in response to a wide variety of growth factors, such as insulin or insulinlike growth factor I (IGF-1), but also in response to DNA damage (Fang et al, 2001;Zhao et al, 2004;Viniegra et al, 2005). Constitutive activation of Akt has been shown to mediate resistance to chemotherapy or radiotherapy (Knuefermann et al, 2003).…”
Section: Discussionmentioning
confidence: 79%